Features of vertebral arteries pathology at trauma - V. V. Shchedrenok; T. V. Zakhmatova; O. V. Moguchaya (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The authors compared results of changes in clinical and radial studies of vertebral arteries in case of trauma of cervical spine. MATERIAL AND METHODS. An analysis of data of complex examination and treatment was made in 157 victims aged 38,5 ± 1,5 years old. RESULTS. Pathology of vertebral arteries was detected in 68,8 % cases. The main ultrasound syndromes were deformations of speed with local hemodynamic significance, compression with systemic deficiency of blood flow, irritative effects, extravasal changes on the level of V-3 segment, thrombosis and dissection. CONCLUSIONS. The development of hemodynamically significant local effects on the vertebral artery depended on degree of stenosis and cross-section area of its canal.